2001
DOI: 10.1097/00004836-200102000-00010
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of Interactive, Multimedia Software for Patient Colonoscopy Education

Abstract: The purpose of our study was to assess the effectiveness of computer-assisted instruction (CAI) in patients having colonoscopies. We conducted a randomized, controlled trial in large, multispecialty clinic. Eighty-six patients were referred for colonoscopies. The interventions were standard education versus standard education plus CAI, and the outcome measures were anxiety, comprehension, and satisfaction. Computer-assisted instruction had no effect on patients' anxiety. The group receiving CAI demonstrated be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
57
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 19 publications
2
57
0
1
Order By: Relevance
“…The nature of the evidence The review and selection process left us with nine papers which met the inclusion criteria: three studies evaluating a videotape intervention (one from the USA [2], one from the UK [26] and one from Australia [4]), and six studies evaluating an interactive computer programme (three from the USA [8,22,25], one from Canada [27] and two from the UK [11,12]). The studies were all good-quality RCTs, with scores ranging from 7 to 5; only one study scored 4 ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of the evidence The review and selection process left us with nine papers which met the inclusion criteria: three studies evaluating a videotape intervention (one from the USA [2], one from the UK [26] and one from Australia [4]), and six studies evaluating an interactive computer programme (three from the USA [8,22,25], one from Canada [27] and two from the UK [11,12]). The studies were all good-quality RCTs, with scores ranging from 7 to 5; only one study scored 4 ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…They were directed at choosing between treatment options [12,25,27], empowering patients to manage their own care [4,8] and facilitating the consent process for recommended procedures [2,11,22,26].…”
Section: Types Of Interventionsmentioning
confidence: 99%
“…Several randomized trials have demonstrated that CAI can increase patients' knowledge about health topics. [13][14][15][16][17][18] We are aware of no studies examining whether CAI can improve CRC screening rates. We hypothesized that CAI could educate patients about FOBT screening more effectively than individual counseling sessions and thereby increase the likelihood that patients will complete the screening procedure.…”
mentioning
confidence: 99%
“…However, no studies have specifically examined the effectiveness of such interventions on surrogates' understanding of informed consent for genomics research in the ICU. We found 9 high-quality studies [19][20][21][22][23][24][25][26][27] in which investigators examined a computer-based educational intervention and the outcome (understanding informed consent), but the researchers focused on procedures, a medical treatment, or non-ICU research and rarely used a surrogate. Computer-based educational interventions have been effective in enhancing understanding of the process of informed consent in procedural studies (cardiac catheterization, colonoscopy, endoscopy with parent as surrogate, and gastric banding surgery) and in a study on medical treatments (chemotherapy).…”
mentioning
confidence: 99%
“…Computer-based educational interventions have been effective in enhancing understanding of the process of informed consent in procedural studies (cardiac catheterization, colonoscopy, endoscopy with parent as surrogate, and gastric banding surgery) and in a study on medical treatments (chemotherapy). [19][20][21][22][23] Additionally, 4 studies [24][25][26][27] focused on non-ICU research: 1 involved a cancer clinical trial, 1 had a sample composed of schizophrenic patients, 1 had patients' parents as surrogates in high-and low-risk clinical trials, and 1 was a genetic tissue repository study. Results were mixed.…”
mentioning
confidence: 99%